Faktor Yang Mempengaruhi Keinginan Investasi Investor Muda di Pasar Modal Indonesia - Aprayuda, Riyadi; Misra, Fauzan (E-Jurnal Akuntansi; Vol 30 No 5 (2020), 2020)
This study aims to examine the influence of attitudes, the impact of the social environment, and investment knowledge on the desire to invest in the capital market by young investors. Specifically, this study refers to the predictors of Theory of Planned Behavior (Ajzen, 1991) to establish factors that influence investment desires. This study uses primary data from a closed questionnaire, with 166 valid responses through online surveys from investors in several university investment galleries in Indonesia. Data were analyzed using Structural Equation Modeling (SEM). The results showed that the attitude of investors and investment knowledge influence the desire to invest. However, the impact of the social environment did not succeed in triggering the investment desire of young investors. These finding underscores the influence of the social environment only being a support, meanwhile, the internal factors of the individual are the main ones making young investors want to invest. As a practical contribution, these finding suggest a positive attitude and increase investment-related knowledge can be applied as a strategy to attract new investors in the capital market . Keywords: Investment Intention; Investor's Attitude; Social Environmental Impacts; Investment knowledge; Young Investor.